Energy Economy, Finance and Geostrategy (Springer International Publishing, 2018)
This volume investigates the impact of energy issues on geostrategy. The crucial importance of energy and the fact that fossil fuels are not equally distributed among countries means that decisions are not only based on financial arguments, but also on the political impact. It can be said that "Energy is Politics". In three parts - 1) Energy Economy; 2) Finance; and 3) Geostrategy - academics and practitioners address both economic and political questions and present cases from several countries. This is the sixth volume in a series on energy organized by the Centre for Energy and Value Issues (CEVI). The previous volumes in the series were: Financial Aspects in Energy (2011), Energy Economics and Financial Markets (2012), Perspectives on Energy Risk (2014), Energy Technology and Valuation Issues (2015) and Energy and Finance (2016).